Videotape in stress intervention among couples a descriptive study - Esteban, Zenaida C. 1936- (1987)
This study attempts the reduction of conflict escalation between couples by learning to manage one of the most common symptoms of stress in the military family--anger. The study used a videotape to achieve the objective.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Video tapes -- Psychological aspects; Stress (Psychology).